Phytochemical and Therapeutic Studies of the Fruit Essential Oil of Thujaorientalis from Nigeria (Global Journal of Science Frontier Research, 2015)
The aim of this study was to establish correlations between the identified phytocompounds in the fruit essential oil of Thuja orientalis from Nigeria and their medicinal properties (free radical scavenging, antioxidant and antimicrobial). Forty-seven compounds were identified in the fruit essential oil of T. orientalis making up 97.5% of the total percentage composition. The essential oil was predominantly made up of monoterpenoids (62.2%). The most abundant components was 1R-α-pinene (15.2%) followed by α-pinene (9.6%), 1S-α-pinene (5.6%), cyclofenchene (5.6%), (+)-3-carene (4.5%), DL-pinene (4.5%) and trans-β-ocimene (4.0%). The high amount of terpenoids leads to more potent radical scavenging, antioxidant and antibiotic properties. The essential oil showed high potential as natural antioxidant and free radical inhibitor with IC50 value: 2.5μgml-1, the percentage inhibition of free radical ranged between 68-70%. Screening of the fruit essential oil for antimicrobial activities using the agar-well diffusion assay showed that the oil had high antibacterial properties against all bacteria isolates tested with zones of inhibition ranging from 10-30 mm.
Keywords: Thuja orientalis; fruit essential oil; phytochemical; antioxidant; antibacterial